INVENTARISASI KERUSAKAN JALAN AKIBAT KENDARAAN DI PRAYA KOTA DESA LENDANG APE KABUPATEN LOMBOK TENGAH - APRILIUS MORI ATE; NI PUTU TITIN SUARTINI; NI MADE NIA BUNGA SURYA DEWI; KUSMIANTI KUSMIANTI (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2023)
This research aims to find out what types of damage are dominant on urban roads in the Praya area, to determine the value of the damage conditions on each road segment that is examined, and to find out the order of priority for road handling and repair. This research includes survey research conducted on roads in the urban area of Central Lombok, so 10 points were taken. Road segments as a sample with a section width of ≥ 5 meters and a road length of 5000 meters. The research results from 1 urban road segment in Central Lombok district which has a total volume of damage of 192.25 m2. The most dominant type of road damage is fine cracking with a total damage area of 60.65m2 with a percentage of 30.59%. Traffic conditions with the most dominant number of vehicles, especially cars, are 1200 consisting of public transportation and pick-ups